2021
DOI: 10.1007/s10120-021-01195-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimized PD-L1 scoring of gastric cancer

Abstract: Background PD-1/PD-L1-Immunotherapy has been approved for gastric carcinoma. PD-L1 assessment by immunohistochemistry is the principle biomarker. Are biopsies able to map the actual PD-L1 status of the entire tumor? Methods Whole tumor slides of 56 gastric carcinoma were analyzed to determine the distribution of PD-L1 positive cells in the entire tumor areas. Tissue micro arrays with four cores of the tumor surface, which represents the endoscopically acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 23 publications
0
34
0
2
Order By: Relevance
“…Although the consensus on PD-L1 positivity is lacking in NEN, CPS 1 is considered a cutoff value for ICI treatment in gastric cancers, cervical cancers, and head and neck squamous cell carcinomas [ 42 , 43 , 44 ]. As we classified, regarding the cases based on the PD-L1 CPS 1, the PD-L1 CPS ≥ 1 subgroup showed significantly higher intra-tumoral, stromal, and combined TIL densities, compared to the PD-L1 CPS < 1 subgroup (intra-tumoral TIL: 7.13/mm 2 (2.89–17.18) vs 2.95/mm 2 (1.62–6.44), p < 0.001; stromal TIL: 200.9/mm 2 (97.12–432.24) vs 120.5/mm 2 (69.14–257.16), p < 0.001; combined TIL: 86.7/mm 2 (47.06–201.31) vs 56.1/mm 2 (33.81–110.12), p = 0.004) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the consensus on PD-L1 positivity is lacking in NEN, CPS 1 is considered a cutoff value for ICI treatment in gastric cancers, cervical cancers, and head and neck squamous cell carcinomas [ 42 , 43 , 44 ]. As we classified, regarding the cases based on the PD-L1 CPS 1, the PD-L1 CPS ≥ 1 subgroup showed significantly higher intra-tumoral, stromal, and combined TIL densities, compared to the PD-L1 CPS < 1 subgroup (intra-tumoral TIL: 7.13/mm 2 (2.89–17.18) vs 2.95/mm 2 (1.62–6.44), p < 0.001; stromal TIL: 200.9/mm 2 (97.12–432.24) vs 120.5/mm 2 (69.14–257.16), p < 0.001; combined TIL: 86.7/mm 2 (47.06–201.31) vs 56.1/mm 2 (33.81–110.12), p = 0.004) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…This method was developed after studies had shown that TPS alone is not a useful predictive biomarker for treatment response and MIDS is not easily reproducible, although it is useful. These two methods combined proved to be a robust and reproducible modality for scoring PD-L1 in tumors [ 16 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The approval of trastuzumab for Her2Neu-expressing tumors and nivolumab as a checkpoint inhibitor for PD-L1-expressing tumors were big advantages in the treatment of AGE/S in recent years [ 30 , 31 ]. Unfortunately, only a few patients are eligible for these new therapy options: the predictive biomarker Her2Neu is expressed in approximately 18% of AGE/S tumors [ 32 ], and about 28% of gastric cancer are eligible for checkpoint inhibition by having a sufficient PD-L1 expression with a combined positive score >5 [ 33 ]. In all published patient cohorts, about 60% of the population were MACC1-positive, and in our study, 79% were positive.…”
Section: Discussionmentioning
confidence: 99%